Simulated deforestation versus satellite data in Roraima, Northern Amazonia, Brazil - Barni, Paulo; Barbosa, Reinaldo Imbrozio; Manzi, Antônio Ocimar; Fearnside, Philip Martin (Sustainability in Debate, 2020)
Scenarios for land-use and land-cover change in Amazonia are necessary to support decisions that could prevent the emission of millions of tons of CO2 into the atmosphere. It is therefore important to evaluate models designed to generate future scenarios. The present study evaluated scenarios generated for the 2011-2017 period in Roraima state, in northern Amazonia. Simulated deforestation was compared to PRODES satellite data. The mapping comprised (i) a “silvopastoral use area” (excluding indigenous lands, conservation units and non-forest areas) intersected with (ii) a grid of nine (9) 10,000 km2 (100 × 100 km) cells for evaluations. The 2013 scenario had the greatest similarity (55.2%) with the corresponding PRODES map. Despite divergences between simulated deforestation in the scenarios and PRODES deforestation, the evaluations generally demonstrated the model’s validity and its ability to produce future scenarios that realistically represent the deforestation that occurred in Roraima state during the analyzed period.